Clinical Features of Critical Coronavirus Disease 2019 in Children*. Issue 10 (October 2020) - Bhumbra, Samina; Malin, Stefan; Kirkpatrick, Lindsey; Khaitan, Alka; John, Chandy C.; Rowan, Courtney M.; Enane, Leslie A.
Abstract : Objectives: We sought to describe the presentation, course, and outcomes of hospitalized pediatric coronavirus disease 2019 patients, with detailed description of those requiring mechanical ventilation, and comparisons between critically ill and noncritical hospitalized pediatric patients. Design: Observational cohort study. Setting: Riley Hospital for Children at Indiana University Health in Indianapolis in the early weeks of the coronavirus disease 2019 pandemic. Patients: All hospitalized pediatric patients with confirmed coronavirus disease 2019 as of May 4, 2020, were included. Interventions: Patients received therapies including hydroxychloroquine, remdesivir, tocilizumab, and convalescent serum and were managed according to an institutional algorithm based on evidence available at the time of presentation. Measurements and Main Results: Of 407 children tested for severe acute respiratory syndrome-coronavirus 2 at our hospital, 24 were positive, and 19 required hospitalization. Seven (36.8%) were critically ill in ICU, and four (21%) required mechanical ventilation. Hospitalized children were predominantly male (14, 74%) and African-American or Hispanic (14, 74%), with a bimodal distribution of ages among young children less than or equal to 2 years old (8, 42%) and older adolescents ages 15–18 (6, 32%). Five of seven (71.4%) of critically ill patients were African-American ( n = 3) or Hispanic ( n = 2). Critical illness was associated with older age ( p = 0.017), longer duration of symptoms ( p = 0.036), and lower oxygen saturation on presentation ( p = 0.016); with more thrombocytopenia ( p = 0.015); higher C-reactive protein ( p = 0.031); and lower WBC count ( p = 0.039). Duration of mechanical ventilation averaged 14.1 days. One patient died. Conclusions: Severe, protracted coronavirus disease 2019 is seen in pediatric patients, including those without significant comorbidities. We observed a greater proportion of hospitalized children requiring mechanical ventilation than has been reported to date. Older children, African-American or Hispanic children, and males may be at risk for severe coronavirus disease 2019 requiring hospitalization. Hypoxia, thrombocytopenia, and elevated C-reactive protein may be useful markers of critical illness. Data regarding optimal management and therapies for pediatric coronavirus disease 2019 are urgently needed.